Gambaran Tingkat Kecemasan pada Lansia Terhadap Penyakit Stroke Di Puskesmas Ponorogo Selatan - Eky Okviana Armyati; Dwi Nurwulan Pravitasari (Syntax Corporation Indonesia, 2022)
Sroke is a frightening disease for anyone. Stroke is a clinical syndrome that has a sudden onset, is progressive, rapid, in the form of a focal or global neurologic deficit lasting 24 hours or more or immediately causes death, and is solely caused by a non-traumatic cerebral blood circulation disorder. In this study, data analysis was carried out using descriptive statistics, namely statistical calculations to describe and synthesize data. By using this statistical procedure evaluate, conclude, organize, interpret and present clear information with meaningful figures. In this study, the researcher used a descriptive research method, namely describing urgent events that occur in the present. Stroke is also known as cerebrovascular disease. This disease shows the presence of several brain abnormalities both functionally and structurally caused by pathological conditions of the cerebral blood vessels or of the entire cerebral vascular system. This pathology causes bleeding from a tear that occurs in the vessel wall or damage to the cerebral circulation by partial or complete occlusion of the vessel lumen with temporary or permanent effects. According to the etiology of stroke are as follows: Brain Infarction (80%).